Genetic data suggest gene flow within a narrow hybrid zone between two recently separated species in the genus Parnassius (Lepidoptera: Papilionidae) - Paolo Gratton; Valentina Todisco; Donatella Cesaroni; Valerio Sbordoni; Vazrick Nazari (PLoS ONE, 2025)
Length polymorphism analysis of six microsatellite loci for 540 Clouded Apollo butterflies from Italy and Switzerland revealed a clear separation between sister species Parnassius mnemosyne and P. turatii and provided updated limits for their respective ranges. Correspondence analysis and Structure clustering of a subset of 140 individuals from the Eastern Alps determined intermediate genetic makeup for three small samples collected in the mid Piave valley (northern Italy). The genotypes of the intermediate individuals are not consistent with F1 hybrids, hinting at clinal genetic variation. Our data indicate a narrow introgression zone with a shallow depth of 50–100 km in what is likely to be the only area of contact between the proposed species P. mnemosyne and P. turatii. Our findings indicate incomplete reproductive isolation between the two species, and are consistent with selection against hybrids or with a recent establishment of a secondary contact. The latter may result from slow recolonization of the Eastern Alps from glacial refugia or from very recent changes in traditional land management practices such as grazing and mowing at semi-natural grasslands.